PENGARUH SARANA WISATA TERHADAP KEPUASAN PENGUNJUNG DI OBJEK WISATA NGALAU INDAH KOTA PAYAKMBUH - Juniva, Silzia; Silfeni, Silfeni; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
The purpose of this research is to determine the influence of tourism facilities towards visitors satisfaction at tourism object Ngalau Indah Payakumbuh. The type of research is associative causal. With the a purposive sampling as much 97 people. Data collection using question based on likert scale that has been tested for its validity and reliability. The result of this research were: (1) Tourism facility located on a enough (63.9%), (2) Visitor satisfaction is in the category less satisfied (86.6%), (3) the result for simple linear regression are on the 0.039 <0.05, then the variable of tourism facilities have a significant effect on the visitors satisfaction. Research show the R Square of 0.044. Which means that tourist facilities affected visitor satisfaction of 4.41%. While 95,59% were affected by other factors.Keywords: Tourist Facilities and Visitor Satisfaction